Identification of amadori products and oligosaccharide-glycated amino acids in brewer’s spent grain extract - Minestrini, Martina; Charton, Sophie; Iken, Marcus; Larondelle, Yvan; Renaut, Jenny; Hausman, Jean-Francois; Sergeant, Kjell (Frontiers in Food Science and Technology, 2022)
Brewer’s spent grain (BSG) is the most abundant by-product of the brewery industry. Its accessibility and chemical composition allow this material to be recycled for new applications mainly targeting the food industry, based on the health-promoting properties of phenolics in BSG extracts. This study investigates the major compounds identified in food-grade extracts from BSG by UHPLC-ESI-MS/MS analyses, with a focus on the presence of Amadori products. These fructosyl-derivatives are identified for most of the proteinogenic amino acids but for instance also for gamma-aminobutyric acid. While previously proposed to be formed, we show that Amadori products are formed by reaction of amino acids with oligosaccharides up to five hexoses. Moreover, the same glycation pattern was also observed for other nitrogen-containing compounds such as phosphatidylethanolamine lipids. The presence of these Maillard reaction products and glycated forms of amino-compounds, due to heat-treatment during brewing or stabilization of BSG prior to further processing, may impact the valorization of this by-product and should thus be considered in future studies.